School Literacy Program: A Lesson Learned From English Language Teaching At A Senior High School - Dika Maharani; Anita Triastuti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This study aimed to describe: (1) the implementation of the School Literacy Program as implemented in English language teaching at a state senior high school in Yogyakarta, and (2) the problems faced by the English teachers in implementing the program in their English language teaching, and (3) the efforts done by the teachers in implementing it in their instructions.This qualitative research study involved the English teachers and grade X students of a state senior high school in the Special Territory of Yogyakarta. The data collection techniques employed were observation, interviews, and documents. The selected unit analyses of data were qualitatively analyzed and coded so as to obtain patterns for inferring findings.The present study has confirmed the following findings: (1) the literacy activities in English lessons were well implemented by the English teachers, (2) the students’ low interest in reading, insufficient ability in reading, and less confidence in speaking was the problems nuanced in the program implementation, and (3) a library visit in which the students were involved in particular extensive reading activities as part of the teachers’ strategy to solve the problems.